The Influence of Alfagift Digital Services on Alfamart Customer Satisfaction (Study in communities throughout Greater Bandung) - Indri Wulandari (International Journal Administration, Business & Organization, 2023)
This research aims to find out whether there is an influence on Alfagift's digital services on Alfamart customer satisfaction. The respondents of this research are people throughout Greater Bandung Indonesia who use the Alfagift application from Alfamart. Data was collected using Google Form and a research sample of 120 respondents was obtained. This research uses quantitative descriptive analysis methods by testing variables using validity and reliability tests and data analysis using frequency, correlation and simple linear regression. The results of this research show a correlation value of 0.829 with a significance of 0.000, which is quite a high correlation. Simple linear regression analysis shows an R Square value of 0.688 with a significance of 0.000 < 0.05. Thus, the results of this research show that there is a positive and significant influence regarding Alfagift's digital services on Alfamart customer satisfaction in the community throughout Greater Bandung, Indonesia